After the atomic bomb: Hibakusha tell their stories. (16th May 2016) - Unknown
Abstract : In this issue, the Review has chosen to feature the voices of hibakusha, those who survived the nuclear bombings in Japan.* These three hibakusha have shared their experiences with the hope that our readers will understand the horrors of nuclear weapons use. They have each suffered and witnessed the horrific suffering of others caused by nuclear weapons, and their families may continue to suffer medical problems for generations to come. Each calls for assurances that nuclear weapons will never be used again. These are their stories.